AIMS-THERMAL - A THERMAL AND HIGH RESOLUTION COLOR CAMERA SYSTEM INTEGRATED WITH GIS FOR AERIAL MOOSE AND DEER CENSUS IN NORTHEASTERN VERMONT - Millette, Thomas L; Slaymaker, Dana; Marcano, Eugenio; Alexander, Cedric; Richardson, Leif (Lakehead University, 2011)
This paper describes a simultaneously firing dual camera system that integrates a new generation radiometric thermal camera with a high spatial resolution natural color camera where all imagery is spatially indexed with local coordinates and managed by a GIS. A test of the system to estimate the moose population in northeastern Vermont found that the Airborne Imaging Multispectral Sensor (AIMS) Thermal system performed well under both overcast and sunny conditions; overcast conditions produced far fewer false-positive heat signatures than older systems. Tests for detection rates in hardwood stands indicated 100% accuracy. Tests to determine if camera lens parallax produced different probabilities of detection inside and outside of the image nadir due to the screening effect of trees indicated no such bias. The estimated moose density was 0.85 moose/km2 based on a 20% sample (136 km2) of the 682 km2 study area, and was within 5% of the pre-survey estimate. Future analysis will include testing of sightability in coniferous habitats.